1986
DOI: 10.1080/02786828608959105
|View full text |Cite
|
Sign up to set email alerts
|

Charged Particle Collection by an Oppositely Charged Accelerating Droplet

Abstract: A theoretical model is derived to predict the collision efficiency of an accelerating droplet under the combined effects of inertial impaction and electrostatic attraction. The calculated efficiencies are reported as a function of the distance traversed by the droplet. This model is indirectly verified by measuring the total particle mass collected by an accelerating droplet. Applications of the proposed model are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…It should be noticed that the experimental results are not available for the Stokes number larger than 2. The collection efficiency measured by Schmidt (86) and Wang (60,61) was for small Coulomb numbers (<≈0.5), and although it increases after particle and droplet charging, it is still below 1. Hara et al (87) obtained the results for a constant Stokes number (a constant flow), which can be estimated to 1.8, and the Coulomb number varying in the range from 0.34 to 4, but the Reynolds number is unknown.…”
Section: Fundamental Experimentsmentioning
confidence: 96%
See 1 more Smart Citation
“…It should be noticed that the experimental results are not available for the Stokes number larger than 2. The collection efficiency measured by Schmidt (86) and Wang (60,61) was for small Coulomb numbers (<≈0.5), and although it increases after particle and droplet charging, it is still below 1. Hara et al (87) obtained the results for a constant Stokes number (a constant flow), which can be estimated to 1.8, and the Coulomb number varying in the range from 0.34 to 4, but the Reynolds number is unknown.…”
Section: Fundamental Experimentsmentioning
confidence: 96%
“…Beizaie and Tien (59) concluded that the gravity is dominant for the particles co-flowing with gravity vector. Wang et al (60,61) considered the problem of particle deposition on a collector falling in a flowing gas, but their theoretical results were restricted only to two dimensions. Additional forces due to external electric field produced by a pair of electrodes were considered by Sumiyoshitani (62), Wang (63), and Shapiro and Laufer (64).…”
Section: Collection Efficiencymentioning
confidence: 99%
“…In the first stage, the motion of particles is mainly affected by gravity force, drag force and electrostatic force. Their trajectories have been observed experimentally (Sumiyoshitani et al 1984;Jaworek et al 2001) or predicted numerically (Wang et al 1986;Adamiak et al 2001;Jaworek et al 2002;Balachandran et al 2003). The interactions between particles and charged droplet surface in the second stage determine the deposition efficiency.…”
Section: Introductionmentioning
confidence: 96%
“…For opposite-polarity, charged-droplets and charged-particles WES, particles deposit onto the droplet due to electrostatic attraction forces. Many studies, including numerical simulations (Pilat et al 1974;Wang et al 1986;Jaworek et al 1997Jaworek et al , 2002Kojevnikova and Zimmels 2000;Yang et al 2003;Zhao and Zheng 2008;Carotenuto et al 2010) and experimental tests (Kraemer and Johnstone 1955;Balachandran et al 2003;Jaworek et al 2006b;Krupa et al 2013), suggest that droplet-target deposition of the particles is more effective. One important reason is that the distances of deposition from particles to droplets are much closer than to chamber walls, closer distance in turn strengthens the electrostatic attractions.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation models for predicting the collision and col lection of the particles on collectors in the presence of electrostatic fields have been available in open literature over the last few decades ( ). These studies provided the basis for modeling the effect of electrostatic field on particle collection by a moving fluid.…”
Section: Introductionmentioning
confidence: 99%